Evaluating a computational thinking and computing attitudes instrument for educational purposes - Oliveira, Eduardo C.; Correia, Ronaldo C.M. [UNESP]; Bittencourt, Roberto A. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper explores a survey instrument on Computational Thinking (CT) and attitudes towards Computing for educational purposes. Given the well-known skills demanded for the 21st century, CT needs to be known in the teacher community. One crucial aspect in this regard is the perceptions that students hold on the subject as well as on Computing in general. Various studies have been carried out to measure students' attitudes towards Computing. However, assessing the understanding of CT and Computing attitudes in undergraduate education, and particularly in teacher education, has not been fully explored yet. Most current instruments are either not aimed at educators or not designed to cover elements related to both CT and Computing. In this work, our goal was to evaluate a survey instrument on perceptions of CT and attitudes towards Computing for undergraduate students. Our evaluation focused on verifying whether the instrument could grasp the aspects involved in five different intended constructs: 1) understanding of CT, 2) application of CT in classroom, 3) confidence to learn Computing, 4) interest for Computing and 5) perception of Computing usefulness. After applying the instrument with 2, 290 undergraduate students, we computed its reliability and used confirmatory factor analysis results to measure its validity. Results showed evidence that the instrument is both reliable and valid to measure impressions of CT and Computing attitudes in an educational context.